An analysis of the ferroelastic transition in Pb(Zr0.53Ti0.47)O3:Gd through the elastic stiffness constant. (4th May 2021) - de Armas Figueroa, Y.; Portelles, J.; López-Noda, Rene; Fuentes, J.; Hmŏk, H'Linh; Siqueiros, Jesús M.
ABSTRACT: The c 66 E values of PZT53/47 doped with 0.6% Gd2 O3 show an anomalous behavior near 132°C as a consequence of a ferroelastic transition. A non-linear fit to the experimental data of the elastic stiffness variation Δ c 66 E shows that it behaves according to the theoretical law describing pseudoproper ferroelastic transitions. Through Raman spectrum analysis, the frequency of soft mode A1 (1TO) has a minimum in the 132–136°C temperature interval associated with the coupling to the S 6 component of the deformation. The quantitative evaluation of the order parameter by hard mode spectroscopy ratified the occurrence of a ferroelastic phase transition. The behavior of both piezoelectric coefficients d31 and the electromechanical coupling factor k31 can be taken as evidence of the transition showing local maxima at 138°C as a consequence of the maximum deformation during the oscillations of the A1 (1TO) mode.